Magnitude of Neonatal Hypothermia and Its Risk Factors Among Hospitalized Neonates in Southern Ethiopia - Anteneh Gashaw; Hunduman Bedada; Eyob Abera (International Journal of Pediatrics)
Conclusion: The prevalence of neonatal hypothermia in the study area was found to be 54%. Factors associated with neonatal hypothermia included labor induction, home delivery, and complications during pregnancy.